THE DILEMMA OF THE DEBT SYSTEM IN GROCERY STORE: BETWEEN INCREASING CONSUMER PURCHASING POWER AND SELLER FINANCIAL MANAGEMENT (A STUDY OF GROCERY STORE IN TELUKNAGA DISTRICT) - Iman Fauzi Sudirman; Han Han Burhani; Nina Farhana Yushof (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the dilemma of implementing a debt system in grocery stores in relation to increasing consumer purchasing power and managing vendor finances. The debt system is a common practice in micro-enterprises based on trust and social relations, especially among low-income communities. The research method used was a qualitative approach with a case study design at a grocery store in Teluknaga District. Data were obtained through in-depth interviews, observations, and documentation of the store owners and customers, then analyzed using the Miles and Huberman model. The results show that the debt system plays a significant role in helping consumers maintain purchasing power and meet basic needs amid economic constraints. In addition, this practice can also increase customer loyalty and strengthen social relationships between sellers and consumers. However, the debt system also poses various challenges for sellers, particularly related to cash flow management, increased risk of bad debts, and hampered business capital turnover. This condition creates a dilemma for business actors between maintaining social relationships with customers and maintaining business financial stability. Therefore, a more structured debt management strategy is needed, such as limiting the amount of debt, systematic record-keeping, and payment monitoring to minimize risks without eliminating the social function of the debt system. This research contributes to understanding the dynamics of the informal economy and decision-making in micro-enterprises.